Islamic Identity in the Digital Era: A Study on the Spirituality and Online Lifestyle of Zillennials - Nur Alhidayatillah; Masduki Masduki (Jurnal Dakwah Risalah, 2025)
The Islamic identity of Zilenial Muslims has undergone a significant transformation in the digital era, where spirituality is not only manifested through ritual practices but also expressed as part of an online lifestyle. This study aims to examine the relationship between digital literacy and the construction of Zilenial Islamic identity, employing UNESCO’s (2011) framework of access, evaluation, creation, and digital ethics. Using a sequential explanatory mixed-method approach, data were collected from one hundred respondents aged 18–25 through surveys and interviews. The findings indicate that almost all participants actively engage with social media for spiritual practices such as sharing Qur’anic reflections, short da’wah messages, and personal contemplations. Many respondents integrate Islamic fashion, lifestyle content, and religious self-branding as essential elements of their online presence. Nevertheless, only about half demonstrated strong critical evaluation skills in filtering Islamic information, while others remain vulnerable to misinformation and algorithmic influence. This study highlights that digital literacy plays a crucial role in maintaining the balance between spirituality and the online lifestyle of Zilenial Muslims.